Assessment of the Impacts of Climate Change on Mountain Hydrology : Development of a Methodology through a Case Study in the Andes of Peru - Vergara, Walter; Deeb, Alejandro; Leino, Irene; Kitoh, Akio; Escobar, Marisa (World Bank, 2012)
The objective of study of the impacts of climate change on mountain hydrology is to develop a methodology to assess the net impacts of climate change on the hydrological response in mountainous regions. This is done through a case study in the Peruvian Andes. There are few examples of predictions of the impact of climate change on resource availability and even fewer examples of the applications of such predictions to planning for sustainable economic development. This report presents a summary of the efforts of a Bank energy and climate change team to develop methodological tools for the assessment of climate impacts on surface hydrology in the Peruvian Andes. The importance of analyzing the potential climate impacts on hydrology in Peru arises in part from concerns about the retreat of tropical glaciers, the drying of unique Andean wetland ecosystems, as well as increased weather variability and weather extremes, all of which will affect water regulation. The study, together with a recently published report by the World Bank, Peru Overcoming the Barriers to Hydropower, is intended to inform plans for energy development in Peru and enable provides some insights into how hydrology may behave under future climate scenarios in Peru, the main purpose is to contribute to the methodological approaches to anticipate impacts from climate change in the Andes Region and other mountain ranges